Pengaruh Islamic Branding Dan Religiusitas Terhadap Perilaku Pembelian Konsumen Kopi Hpai Di Kota Pekanbaru Perspektif Ekonomi Islam - Mailisa Mailisa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to observe the influence of Islamic branding and religiosity towards the customer behavior in purchasing the HPAI coffee in Pekanbaru city in accordance with Islamic economic perspective. There were 155 respondents involved in this research. The research method used in this research was the quantitative method using the prophetic paradigm. The data used was primary data and the analysis tools was PLS with the SmartPLS 3.0 software. The results of this research showed that the role of Islamic branding towards the purchasing behavior of customers had a positive impact on the purchasing behavior of customers. Attitude and subjective norms also has a positive impact on the intention of the customers of HPAI coffee but the perception of the behavior control and religiosity showed no positive impact on the intention and the purchasing behavior of customers. In this research, religiosity of customers of HPAI coffee did not moderate the relationship between Islamic branding and the purchasing behavior of customers.